2020
DOI: 10.1149/1945-7111/abaf74
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Surface Strain for Enhanced Carbon Dioxide Reduction on Copper-Silver Alloys

Abstract: The electrochemical reduction of atmospheric carbon dioxide to value added chemicals and fuels using renewable energy is a promising route to a sustainable economy. In this work we present results from the electrochemical reduction of carbon dioxide on copper/silver alloy electrodes alongside pure copper and pure silver in acetonitrile-water electrolyte mixtures. EIS measurements show that the copper/silver alloys exhibit lower charge-transfer resistance when compared to the pure metal electrodes. Reduced prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Electroreduction is a widely used method for reducing CO 2 emissions. Research in this eld has been actively progressing recently, with studies reporting the obtainment of valuable products from CO 2 using electrodes such as Cu, Ag, and Au in aqueous solutions, where the faradaic efficiency reached >60%; [3][4][5][6][7] however, many occasions of overvoltages (1-2 V) have been reported as well. Under such circumstances, evaluating the CO 2 reduction using faradaic efficiency is not worthwhile, when compared to other energy conversion methods, e.g., water electrolysis for hydrogen energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Electroreduction is a widely used method for reducing CO 2 emissions. Research in this eld has been actively progressing recently, with studies reporting the obtainment of valuable products from CO 2 using electrodes such as Cu, Ag, and Au in aqueous solutions, where the faradaic efficiency reached >60%; [3][4][5][6][7] however, many occasions of overvoltages (1-2 V) have been reported as well. Under such circumstances, evaluating the CO 2 reduction using faradaic efficiency is not worthwhile, when compared to other energy conversion methods, e.g., water electrolysis for hydrogen energy production.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is imperative to develop remarkable electrocatalysts which significantly speed up the reaction rate and regulate the reaction selectivity toward the target products [16,17]. To date, different types of metal-based electrocatalysts such as Au [18][19][20][21][22][23], Cu [24][25][26][27][28][29][30][31][32][33][34][35][36], Pd [37][38][39][40][41][42][43][44][45][46], Ag [47][48][49][50][51][52][53][54], Bi [32,[55][56][57][58], Sn [59][60][61][62][63] and Co [64]...…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reports have shown that alloying Cu metal with other metals is an efficient way to accomplish particular products at relatively low overpotential. 13,14 On the other hand, the non-noble Zn metal would be a good candidate for CO 2 reduction due to its abundance, cost-effectiveness, and environmentally benign. 15 Hence, the CO 2 reduction activity of Cu is enhanced by the formation of CuZn alloy since Zn is turned out to be slower for the Hydrogen Evolution Reaction (HER) process.…”
mentioning
confidence: 99%